ANALYSIS OF THE BIM IMPLEMENTATION COMPETENCIES OF BUILDING CLUSTER VOCATIONAL HIGH SCHOOL STUDENTS IN THE EAST JAVA - Irvansyah; Muchlis, Nurfahmi; Suryawan, Wawan Ardiyan (Border: Jurnal Arsitektur, 2022)
Even though the government, through the Ministry of Public Works and Public Housing (PUPR), introduced the concept of Building Information Modeling (BIM) in regulations as a form of collaboration and integration for application in the Indonesian construction industry in 2017, the adoption rate of BIM in Indonesia remains low. There are many obstacles that must be faced, such as the curriculum at the vocational high school level to higher education, or skill sets that have not yet been developed in their users. This study examines the abilities of Building Cluster Vocational High School Students in terms of mastered skills that are in line with BIM competency standards. The methods are a survey and the use of the Relative Importance Index on the participants of the 30th Vocational High School Competency Competition (LKS) at the East Java Provincial Level in 2022. The finding indicates that non-cognitive competencies dominate the adaptability of these students' mastery of BIM software.